Prolonged jaundice in Hepatitis-E patients: going beyond the optics - Butt, Nazish; Afzal, Nayab; Shakeel, Danish (Journal of the Pakistan Medical Association, 2022)
Hepatitis E virus (HEV) is an RNA virus that is transmitted faeco-orally. Due to unhygienic living conditions and unsatisfactory treatment of drinking water, it is a major cause of acute viral hepatitis in Pakistan. Hepatitis E infection in patients with glucose-6-phosphate dehydrogenase (G6PD) deficiency may cause prolonged jaundice resulting in serious complications like, severe haemolysis, acute renal failure, encephalopathy and even demise. Although both these diseases occur frequently in our country there is a dearth of literature on the effect of Hepatitis E infection in G6PD deficient patients, leading to higher rate of complications in such patients. We report a case of 37 years old male who was referred to our hospital with worsening jaundice. Patient had HEV infection with concomitant G6PD deficiency. This case had a different prospect, since it resulted in prolonged jaundice and severe haemolysis. However patient’s condition improved with conservative management.